(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article socio-philosophically analyzes the philosophy of education and its substantive components, genesis, evolution of development, issues of social significance in society. The reasoned subjective activity of the philosophy of education, aimed at updating social life on a rational basis, and scientific approaches to innovative thinking are also analyzed.